Social Media Marketing in Nepal: A Study of Travel Intermediaries of the Kathmandu Valley - Sthapit, Arhan; Khadka, Ishwor (PYC Nepal Journal of Management, 2016)
The paper examines the status of social media marketing activities in Nepal in the context of that of travel intermediaries in the Kathmandu Valley, and specifically probes into three key areas: use of social media in travel intermediary business, influence of social media on customers and customers’ response to social media sites (SMSs). Adopting a mixed study approach, the paper made use of both primary surveys (on travel intermediaries and customers between March-May, 2016) and secondary data search from the former’s SMSs for which a convenience sampling technique was used to choose the intermediaries from the Thamel area, the main travel tourism business hub of Nepal. The study found constant rise in the use of social media by travel intermediaries in communicating about product and price, which customers also most look for and respond to. Facebook alone and Facebook in combination with other social media was most popular among both intermediaries and customers; and SMSs are influential in making most customers buy the mixed category of travel products. What of the SMSs influences the customers most is the recall factor of the sought product information and comments and reviews. The findings can be useful to the travel managers in strengthening their social media marketing.